Nurses' cleaning practice of non-critical medical equipment in the era of COVID 19: A cross-sectional study in Debre-Tabor comprehensive specialized hospital. Issue 7 (July 2021) - Amera Birlie, Tekalign; Amare, Abraham Tsedalu; Tassew, Sheganew Fetene; Emiru, Tigabu Desie; Feleke, Dejen Getaneh; Chanie, Ermias Sisay
Abstract: Objectives: This study was aimed at assessing the cleaning practice of non-critical medical equipment (NCME) in the era of corona virus disease-2019 of nurses working in Debre-Tabor comprehensive specialized hospital (DTCSH), north-central Ethiopia. Design: Facility based cross-sectional study was conducted in DTCSH, Ethiopia, from July 05 to August 05, 2020. Setting: The study was conducted in inpatient and outpatient units of the hospital. Participants: A total of 76 randomly selected staff nurses and 6 head nurses were included for observational study and interview respectively. Results: Only 1.3%–5.3% of nurses cleaned stethoscopes, thermometers, pulse oximeters, and glucometers right after using these devices for patients. None of them cleaned the blood pressure apparatus before or after checking a patient's blood pressure and glucometer before determining blood glucose levels. Lack of disinfecting materials and lack of training on infection prevention were perceived by head nurses as major barriers for proper cleaning practices. Conclusion: Nurses' cleaning practice of NCME was very low. Therefore, proper supply of materials needed to clean these devices need to be secured. Besides, nurses need to get training on infection prevention. Abstract : Nurse, Cleaning, Non-critical medical equipment, COVID 19.